Direct and Indirect Effects of Subsidized Dual Apprenticeships - Crépon, Bruno; Premand, Patrick (Review of Economic Studies, 2025)
Abstract Public interventions in the apprenticeship market often aim to increase demand or returns. We set up a double-sided experiment with youth and firms to analyse a subsidized dual apprenticeship program. This intervention seeks to relax financial constraints for youth by offering a wage subsidy and to make apprenticeship more attractive by providing vocational training in technical skills that complements on-the-job training. We document a large increase in youth participation in apprenticeship, yet the inflow of apprentices induces little crowding out of traditional apprentices in firms. The intervention leads to an increase in youth demand for apprenticeship, enabling firms to fill open apprenticeship positions. The subsidy compensates apprentices for low wages but does not alleviate financial constraints. Consistent with the dual training component contributing to an increase in youth demand for apprenticeship, youth perform more complex tasks and have higher earnings 4 years after the start of the experiment.